Overview of MYH9 Gene Polymorphism SNP RS3752462 in Chronic Kidney Disease (CKD) Patients with Diabetic Nephropathy - Ahmad Akmal Maulana; Muhammad Taufiq Qurrohman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Diabetic nephropathy is a major cause of chronic kidney disease and is influenced by both environmental and genetic factors. One of the genes implicated in the pathogenesis of diabetic nephropathy is MYH9, particularly the Single Nucleotide Polymorphism (SNP) rs3752462. This study aimed to describe the polymorphism of the MYH9 gene SNP rs3752462 in patients with chronic kidney disease associated with diabetic nephropathy. A descriptive study design was applied, involving five patients who met the inclusion criteria. Blood samples were analyzed using the Polymerase Chain Reaction–Restriction Fragment Length Polymorphism (PCR-RFLP) method with the RsaI restriction enzyme. The Results showed that the DNA band patterns observed in all samples did not form consistent combinations and did not correspond to the expected genotype classification standards. In addition, extra bands outside the target fragment sizes and variations in band intensity among samples were observed. Based on these findings, the resulting band patterns could not be reliably used to accurately determine genotypes, and therefore did not adequately represent the polymorphism of the MYH9 gene SNP rs3752462 in the studied samples. Accordingly, further optimization of the PCR-RFLP method is required, along with validation using more accurate approaches, such as DNA sequencing, and a larger sample size to obtain more reliable results.